2021
DOI: 10.3389/fcell.2021.678190
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Regulates the Neurotransmitter Secretion Disorder Induced by Caffeine Through the Microbiota-Gut-Brain Axis in Zebrafish (Danio rerio)

Abstract: Melatonin has been widely used as a “probiotic agent” capable of producing strong neurotransmitter secretion regulatory effects, and the microbiota-gut-brain axis-related studies have also highlighted the role of the gut microbiota in neuromodulation. In the present study, a zebrafish neural hyperactivity model was established using caffeine induction to explore the regulatory effects of melatonin and probiotic on neurotransmitter secretion disorder in zebrafish. Disorders of brain neurotransmitter secretion (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 51 publications
(56 reference statements)
1
17
0
Order By: Relevance
“…30 A GF zebrafish study revealed a potential mode of action where melatonin could regulate disorders of neurotransmitter secretion induced by caffeine via the gut-microbiome-brain axis. 31 Additionally, Cuomo et al documented that the administration of L.…”
Section: The Gut-brain Axismentioning
confidence: 99%
See 2 more Smart Citations
“…30 A GF zebrafish study revealed a potential mode of action where melatonin could regulate disorders of neurotransmitter secretion induced by caffeine via the gut-microbiome-brain axis. 31 Additionally, Cuomo et al documented that the administration of L.…”
Section: The Gut-brain Axismentioning
confidence: 99%
“… 30 A GF zebrafish study revealed a potential mode of action where melatonin could regulate disorders of neurotransmitter secretion induced by caffeine via the gut‐microbiome‐brain axis. 31 Additionally, Cuomo et al documented that the administration of L. rhamnosus in larvae led to DNA methylation code of the Tph1A and BDNF promoter gene reconstruction in the gut and the brain of zebrafish. Accordingly, alterations in the gut microbiome may influence the host epigenetic landscape, resulting in long‐term consequences for specific gene regions.…”
Section: The Roles Of the Gut Microbiome In Tissue Development And Ph...mentioning
confidence: 99%
See 1 more Smart Citation
“…In glyphosatetreated Chinese mitten crab (Eriocheir sinensis), the supply of MEL (80 mg/kg food) as a supplement to the standard feed for 14 days significantly increases the relative abundance and Shannon index of Proteobacteria and Bacteroidete along with an enhanced activity of amylase, lipase, and trypsin in the gut (Song et al, 2020). Further, in zebra fish (D. rerio), 1 µM MEL administration in filtered tank water for 14 days improves metabolism and normal gut microbial homeostasis, and restores neurotransmitter release (Zhang et al, 2021). Bacillus, Lactobacillus, and Escherichia coli constitute the major microbial populations in fish gut and significantly improve various physiological activities during the rearing of fish in aquaculture practice (Carnevali et al, 2004;Hasan and Banerjee, 2020).…”
Section: Impact Of Melatonin On Microbiota In Fish Gutmentioning
confidence: 99%
“…The impact of MEL on fish growth and development in association with digestive physiology are also evident from several studies (Falcón et al, 2003(Falcón et al, , 2007(Falcón et al, , 2010Pal et al, 2016a;Pal and Maitra, 2018). Several lines of evidence suggest that MEL, along with its effect on enhancing the digestive enzyme activity in the gut, has a significant impact on the gut microbiota in fish as well as in other vertebrates (Yin et al, 2018(Yin et al, , 2020Wang et al, 2021;Zhang et al, 2021). A fish study by evincing a role of endogenous MEL in ameliorating microbial infection-induced pathogenesis implicates MEL in aquaculture against ulcer causative agents (Pal et al, 2016b).…”
Section: Introductionmentioning
confidence: 97%